Growth and serum mineral profile of broiler starter fed dried cocoyam tuber (colocasia esculenta) meal - M. U., Onyekwere; P. C., Jiwuba; S. O., Okechukwu; A. C., Anuonye (International Journal of Biological Research, 2016)
A 30-day experiment was conducted with 240 unsexed broiler starters to determine the effect of cocoyam tuber meal on growth and serum mineral profile. Four diets were formulated at 0%, 10%, 20% and 30% of cocoyam tuber meal. The birds were assigned the four treatment diets in a completely randomized design and replicated 3 times with 20 birds per replicate. Feed and water were supplied ad-libitum. Data were collected on average daily feed intake, average daily weight gain, feed conversion ratio and blood was sampled from each treatment group, data obtained were analysed statistically. The performance of the broiler starter birds showed significant (p<0.05) difference among the treatment groups. Average daily weight gain was improved (p<0.05) by cocoyam inclusion at 30% inclusion level. FCR of the birds in treatment groups were significantly (p<0.05) better than the control. The parameters of serum mineral profile maintained a significant (P<0.05) difference among the treatments and showed a good evidence of body structural components of the birds. These results showed that inclusion of cocoyam tuber meal had a beneficial effect on performance and structural components of broiler starters. Cocoyam tuber meal inclusion level at 30% was recommended for optimum broiler starter birds.